Correlation Analysis Between Inundation Depth and Land Cover Change in the Jatiroto Watershed, Lumajang, Indonesia - Nabilla Syafa; Suharyanto, Agus; Wijatmiko, Indradi (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
Understanding how land cover changes influence flood inundation is essential for effective watershed management in rapidly developing areas. This study investigates the correlation between inundation depth and land cover transformation in the Jatiroto Watershed, Lumajang, Indonesia, from 1995 to 2023. Using an integrated hydrologic–hydraulic modeling framework that combines GeoHECRAS and GIS, flood depths were simulated under multiple land-cover scenarios derived from Landsat imagery. Spearman’s rank correlation analysis was then applied to quantify the relationships between inundation depth and specific land cover classes. The results indicate that converting natural vegetation to urban and agricultural uses significantly increased the extent and depth of flood inundation. From 1995 to 2023, flooded areas expanded from 12.88% to 15.66%, while the mean inundation depth increased by approximately 0.4 m. The statistical analysis revealed strong positive correlations between inundation depth and open land (? = 0.819), residential areas (? = 0.757), and wetlands (? = 0.743), whereas forest cover exhibited a strong negative correlation (? = –0.819). These findings demonstrate that the expansion of impervious surfaces directly elevates flood severity, while vegetation plays a vital mitigating role. This study provides a comprehensive understanding of the statistical relationship between land-cover composition and flood behavior, offering valuable insights for flood risk management, zoning policy, and sustainable watershed planning in tropical regions.